New curve sprint test for soccer players: Reliability and relationship with linear sprint - Filter, A.; Olivares, J.; Santalla, A.; Nakamura, F. Y.; Loturco, I.; Requena, B. (Journal of Sports Sciences, 2020)
The speed performance is involved not only in linear sprints, but also in a wide spectrum of multi-directional movements, such as curve sprinting. Curved sprint can be defined as sprint with gradual and continuous change of direction (COD). Although ~85% of the actions performed at maximum velocity in a professional soccer league are curvilinear sprints, there is not any specific test to assess this ability. This study aimed to analyse the reliability of a new curve sprint test, and compare its results with those obtained by soccer players in linear sprint. Forty experienced soccer players performed 3 attempts of curve sprint (using the penalty arc) to right and left side (17 m), and 3 linear sprints (17 m) in two different days. The ICCs (inter-session reliability) were 0.93 for sprint curve right side (CSRS) and 0.89 for sprint curve left side (CSLS), considered "acceptable". The CVs (intra-session reliability) were 0.87% in CSRS and 1.15% in CSLS. The coefficient of determination (R2) between linear and curve sprinting was ~35%. The association between curve sides was "very large" (r = 0.878; p < 0.01). In summary, we showed that "curve sprint test" is highly reliable, and that curvilinear and linear sprints are different and independent actions.